Pelaksanaan Eksekusi Sita Marital Pembagian Harta Bersama Putusan Nomor 385/PDT.G/2020/Pa.Bkn di Pengadilan Agama Bangkinang - Fakhira, Widhah; Rianti, Ratna; Heriyanti , Yuli (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2023)
This study discusses the execution of marital confiscation over the distribution of joint assets (juridical analysis of Court Decision Number 385/Pdt.G/2020/PA.Bkn) at the Bangkinang Religious Court, and the obstacles in carrying out the execution in decision Number 385/Pdt.G/2020 /PA. No. The method used is Observational Research through interviews as a data collection tool. This research is analytical descriptive in nature, which provides a clear and detailed description of an event that occurred. The process of carrying out the execution of marital confiscation over the distribution of joint assets based on Court Decision Number 385/Pdt.G/2020/PA.Bkn cannot be carried out because the plaintiff withdrew the application for confiscation of execution. The obstacles faced were that the implementation process cost quite a lot, the selling value of the object of the case decreased due to an assessment carried out by KJPP, if the auction object was sold, an application for the execution of vacancy which costs more was required, and the distribution of the proceeds from the auction was not in accordance expectations and divided into two parts.